(untitled) (Journal of Social Sciences Review, 2023)
This study sought to examine the role of age and gender in developing Body-Focused Repetitive Behavior Disorders (excoriation, trichotillomania, and nail-biting) among adolescents. The sample(n=130) of this study was comprised of adolescents, including both educated males and females. The scales that were used in the current study are; The Trichotillomania Scale for Children/adolescents (Tolin et al., 2008), skin picking scale (Snorrosam et al., 2012), and Nail-Biting Scale (Claes & Vandereycken, 2007). There was no significant difference found between age and gender with respect to BFRBD. The findings of the study will increase the understanding of the knowledge of critical age period of adolescence with respect to Body focused repetitive disorders. The findings of this study will help psychologists, counselors, psychiatrists, and therapists to design and plan therapeutic interventions for BFRBD.